Heme oxygenase-1 gene rs2071746 polymorphism in retinal vein occlusion. (3rd September 2022) - Posch-Pertl, Laura; List, Wolfgang; Michelitsch, Monja; Pinter-Hausberger, Silke; Berisha, Bujar; Posch, Florian; Kloeckl, Lorenz; Renner, Wilfried; Weger, Martin
ABSTRACT: Background: Heme oxygenase-1 (HO-1) is an important cytoprotective enzyme due to its ability to degrade pro-inflammatory heme. The common single nucleotide polymorphism (SNP) rs2071746 on the HMOX1 gene has been associated with HO-1 activity and a variety of cardiovascular diseases. This study was performed to investigate the association between the rs2071746 SNP and retinal vein occlusion (RVO). Methods: We included 496 RVO patients and 297 control subjects in this case-control study. Genotypes of the rs2071746 polymorphism were determined by TaqMan assays. Results: There was no association between the rs2071746 genotype and the presence of RVO ( p = .443). The lack of association was found in all three logistic regression models, namely the dominant ( p = .560), the recessive ( p = .373) and the co-dominant model ( p = .444). The distribution of the rs2071746 genotype was 30% (AA), 51% (AT), and 19% (TT). Baseline characteristics were similar between these genotypes, except for diabetes mellitus, which was less prevalent in the AA genotype ( p < .001). Conclusion: The rs2071746 polymorphism does not seem to be a major risk factor for the presence of RVO.